Simulation of the Effect of Dy3+ Dopant on the Mass Energy Absorption Coefficient and Relative Energy Response of TLD Made from Lithium Magnesium Borate Using MCNP - Handayani, Nita; Novan Prawira, Dyon; Arianto, Fajar (Jurnal Ilmu Fisika, 2024)
Thermoluminescence dosimeter (TLD) is widely used as a personal and medical dosimeter. Several TLD materials show the characteristics of mass energy absorption coefficient and energy response relative to ICRU (International Commission on Radiation Units and Measurements) issue material as an equivalent material for human body soft tissue. This research aims to analyze the effect of Dy3+ dopant on the mass-energy absorption coefficient and relative energy response of Lithium Magnesium Borate (LMB) materials. The simulation was carried out using Monte Carlo N-Particle (MCNP) software. Calculations based on simulation and theoretical results will be compared statistically using paired t-tests. The study showed that adding a Dy3+ dopant to TLD material made of Lithium Magnesium Borate (LMB) only affected the mass-energy absorption coefficient and relative energy response for low radiation energy. Adding Dy3+ dopant increased the mass energy absorption coefficient and relative energy response in a reasonably small value. Based on these results, LMBDy3+ produces a better mass-energy absorption coefficient value for TLD materials. The results of the statistical tests show a significant difference in the mass energy absorption coefficient value. At the same time, there is no significant difference between the simulation results and theoretical calculations for the relative energy response.